Mass spectrometric immunoassays for discovery, screening and quantification of clinically relevant proteoforms. (August 2016) - Trenchevska, Olgica; Nelson, Randall W; Nedelkov, Dobrin
Human proteins can exist as multiple proteoforms with potential diagnostic or prognostic significance. MS top-down approaches are ideally suited for proteoforms identification because there is no prerequisite for a priori knowledge of the specific proteoform. One such top-down approach, termed mass spectrometric immunoassay utilizes antibody-derivatized microcolumns for rapid and contained proteoforms isolation and detection via MALDI-TOF MS. The mass spectrometric immunoassay can also provide quantitative measurement of the proteoforms through inclusion of an internal reference standard into the analytical sample, serving as normalizer for all sample processing and data acquisition steps. Reviewed here are recent developments and results from the application of mass spectrometric immunoassays for discovery of clinical correlations of specific proteoforms for the protein biomarkers RANTES, retinol binding protein, serum amyloid A and apolipoprotein C-III.